Pengungkapan Corporate Social Responsibility, Narsisme Direktur Utama dan Manajemen Laba - Putri Dwi Aprilia Nur Khasanah; Indra Wijaya Kusuma (BAJ: Behavioral Accounting Journal, 2022)
This research has a purpose to explain the relationship of corporate social responsibility (CSR) disclosure and earnings management. In addition, this research explains another factor, CEO narcissism for affecting the relationship. This study uses regression analysis with 398 manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2015-2018 as samples by using purposive sampling. Data collection method uses documentation technique for secondary data in Osiris and hand collecting. The results proved that disclosure of corporate social responsibility has a positive correlation with earnings management. The higher the corporate social responsibility disclosure, the higher the level of earnings management intensity. This result provides that it is stronger for companies with narcissism CEOs. This research has a contribution as a literature reference for corporate governance and behavior in company. This research uses GRI as corporate social responsibility indicator. For further research, it can be used a more comprehensive measurement to explain the relation between organization culture and company type.